2009
DOI: 10.1016/j.jep.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Antipyretic and anti-inflammatory properties of the ethanolic extract, dichloromethane fraction and costunolide from Magnolia ovata (Magnoliaceae)

Abstract: Collectively, these results show, for the first time, that extracts obtained from Magnolia ovata possess antipyretic and anti-inflammatory properties, and costunolide appears to be the compound responsible for these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 33 publications
0
62
0
Order By: Relevance
“…The oral administration of costunolide inhibited carrageenan (Cg)-induced paw edema ) mg/ kg) and was effective in abolishing lipopolysaccharide (LPS)-induced fever (0.15 mg/kg) (Kassuya et al, 2009).…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…The oral administration of costunolide inhibited carrageenan (Cg)-induced paw edema ) mg/ kg) and was effective in abolishing lipopolysaccharide (LPS)-induced fever (0.15 mg/kg) (Kassuya et al, 2009).…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…Costunolide was first isolated from costus roots (Saussurea lappa) (24) and is now found in several plant species, including Magnolia spp. and lettuce (25,26). It is known that costunolide is not only the precursor of STLs but also displays several bioactivities.…”
mentioning
confidence: 99%
“…It is known that costunolide is not only the precursor of STLs but also displays several bioactivities. Reported pharmaceutical activities of costunolide include anti-inflammatory (25), anti-carcinogenic (27), anti-diabetic (28), anti-fungal (29), and anti-viral activities (30). Hence, costunolide can be a valuable chemical feedstock as the precursor of various bioactive STLs.…”
mentioning
confidence: 99%
“…Saussurea costus is considered to be one of the antioxidant-rich medicinal plants. Many authors have reported that the roots of this plant possess various biological activities, including cortisol lowering effect [38], anti-infammatory [39,40], anticancer [41,42], antiviral [23], antimicrobial [43,44], antifungal [15], antioxidant [45,46], antidiabetic [47], antiulcer [20] and hepatoprotective effects [38]. Liv-52 is widely used in treatment of liver diseases of varying origins.…”
Section: Discussionmentioning
confidence: 99%